1985
DOI: 10.1080/01490458509385919
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biomass and productivity in seagrass beds

Abstract: Different methods for measuring the rates of processes mediated by bacteria in sediments and the rates of bacterial cell production have been compared. In addition, net production of the seagrass Zostera capricorni and bacterial production have been compared and some interrelationships with the nitrogen cycle discussed. Seagrass productivity was estimated by measuring the plastochrone interval using a leaf stapling technique. The average productivity over four seasons was 1.28 +/- 0.28 g C m-2 day-1 (mean +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 27 publications
3
37
0
1
Order By: Relevance
“…(Table 6). These rates are comparable to the high end of the range of rates measured in other seagrass environments (Oremland 1975, Moriarty et al 1985.…”
Section: Microbial Decomposition Rates and Pathwayssupporting
confidence: 82%
“…(Table 6). These rates are comparable to the high end of the range of rates measured in other seagrass environments (Oremland 1975, Moriarty et al 1985.…”
Section: Microbial Decomposition Rates and Pathwayssupporting
confidence: 82%
“…Findlay et al (1989) found by direct counts a 3 to 4 times smaller microbial biomass than by phospholipid analysis. The phospholipid content of 1 g bacterial biomass varies between 50 ~mol (Findlay et al, 1989) and 250 [tmol (Moriarty et al, 1985). The factor of the fumigation-extraction method to convert CHC13-1abile C to microbial biomass C is less variable (Kaiser et al, 1992), but also not completely satisfactory because it was calibrated mainly for agricultural soils and not for oxic and anoxic sediments (Jenkinson, 1988;Wu et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The microbial biomass is defined as the sum of organisms smaller than 5 • 103 ~m 3 (Jenkinson & Ladd, 1981) and is recognized as the most important fraction of organic matter in different sediments (Moriarty et al, 1985;Alongi, 1988). Heterotrophic microorganisms mineralize the greatest part of all organic material that enters the sediment ecosystem, converting it to simple inorganic compounds that can be used again by autotrophic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The positive correlation between the SRR and BGB (Fig. 5c) suggested that a substantial amount of dissolved organic carbon (DOC) is released via roots and rhizomes (Moriarty et al 1985;Blackburn et al 1994;Holmer et al 2006). Considering the general positive relationship between the SRR and BGB, further correlation analyses for individual seagrass species revealed that the correlation between the SRR (Fig.…”
Section: Control Of Sulfate Reduction At the Two Seagrass Bedsmentioning
confidence: 96%